Idiopathic male Infertility Caused by DNA Methylation and Genomic Imprinting (Bangladesh Journal of Zoology, 2024)
Epigenetics is the study of changes in organisms caused by genetic control through different factors without alteration of the genetic code itself. Epigenetic inheritance and its under lying molecular mechanisms are the most fascinating areas of current biological and medical research data regarding the epigenetically mediated effects of a man's diet on sperm quality are emerging in the field of human reproductive health. In this regard, epigenetics has become one of the most promising research areas in understanding male infertility. Infertility is the inability to conceive after at least a year of unprotected intercourse which influences about 15% of couples worldwide. The actual cause has not surely revealed yet, hence it is termed as idiopathic male infertility. Many studies have indicated that epigenetic modifications including DNA methylation in imprinted and developmental genes, modifications of histone tail as well as the short non-coding RNAs in spermatozoa may have a role in idiopathic male infertility. The present review aims to assess the significance of DNA methylation in male infertility.Bangladesh J. Zool. 52(2): 217-223, 2024